IMPACT OF AQUACULTURAL ACTIVITIES ON THE SOIL AND WATER QUALITIES OF WETLAND ENVIRONMENT - Patra, Ashok K (Journal of Soil and Water Conservation, 2022)
In India, a dramatic increase in aquacultural productivity has been witnessed in the last two decades because of the use of intensive and modern farming technologies. However, like agriculture, intensive aquafarming is also not free from associated environmental problems. Indiscriminate fluxes of feed derived wastes, pond fertilization, residues of chemicals, etc. are the major sources for potential risk of soil and water degradation of the wetland areas. In this article, impact of aquacultural activities on physico-chemical qualities of soil and water resources has been examined. Hypothetical models for ecological aquaculture, recommendations for' better soil and water qualities and future research areas have also been suggested.